New Method of Heat Compensation for Defrosting of Air Source Heat Pump System in Winter - 陈超; 欧阳军; 王秀丽; 刘铭 (Zhileng xuebao)
Frost removing of air-source heat pump results in shortage of heat output,chilly air flow,and less comfortable interior environment in winter.In our study,a new method to solve the problem of frost-removing in air-source heat pump units was proposed using phase-change energy storage technique.The thermal storage equipment filled with DX40 phase-change material was connected to the air-source heat pump unit.In heating cycle,the heat pump unit provides heat to both indoor air and the phase-change heat storage equipment.In frost-removing cycle,the thermal storage equipment provides heat to indoor air in order to make the room comfortable,the frost-removing quicker,and the unit more efficient.The experimental results show that the air-source heat pump connected with the phase-change thermal storage equipment performs well.